Investigative competence in Business Administration students, public universities - Vera - Pirela, Carlos Alberto; Galvis - Núñez, Carmen Cecilia (Universidad Francisco de Paula Santander, 2022)
The purpose of the following investigation is to review the state of student skills and the investigative attitude of the Business Administration students of the Popular University of Cesar. Due to its importance and attention because it reveals the competitive advantages and shortcomings of future professionals in this area in their university graduation profile. It is necessary to point out that the investigative competences in this type of professionals project them to the success of their career because it facilitates their actions in their professional life; This research aims to analyze the state of investigative skills in business administration students of the Popular University of Cesar, where the technical-instrumental skills and the investigative attitude provided by the students of the Program are involved. This research was typified as descriptive non-experimental transactional and field with a quantitative paradigmatic approach; the technique used for data collection was a survey in which a series of items were formulated aimed at business administration students in the last semesters of the Popular University of Cesar, the results obtained are that they demonstrated certain shortcomings in the state of technical-instrumental skills and investigative skills, although the investigative attitude was also weak. As a final contribution, the characteristics of the investigative attitude and the profile of investigative competencies that are a fundamental part of the life of future professionals should be emphasized.